Clinicopathological analysis of 22 Müllerian adenosarcomas and the sequencing of DICER1 mutation - Xiaohong Yao; Wei Wang; Ying He (BMC, 2024)
Abstract Background Müllerian adenosarcoma, a rare malignancy, presents diagnostic and therapeutic challenges. In this study, we conducted an analysis of the clinicopathological characteristics of 22 adenosarcomas, with a particular focus on screening for DICER1 hot mutations. Methods The cohort consisted of patients with adenosarcoma who were registered at the West China Second Hospital between the years 2020 and June 2022. Sanger sequencing was employed to screen for somatic Hotspot mutations in the RNase IIIb domain of DICER1 in the 22 adenosarcomas. Results Only one patient exhibited a DICER1 mutation that was not a DICER1 Hotspot mutation. Among the 22 patients, all underwent total hysterectomy with bilateral salpingo-oophorectomy, and 14 out of these 22 patients received adjuvant treatment. Conclusion In summary, our study of 22 Müllerian adenosarcomas focused on the clinicopathological features and the presence of DICER1 Hotspot mutations. Although our findings did not reveal any DICER1 mutations in the studied samples, this negative result provides valuable information for the field by narrowing down the genetic landscape of adenosarcomas and highlighting the need for further research into alternative molecular pathways driving this malignancy.